EVALUASI PENGGUNAAN LARVA BLACK SOLDIER FLY (BSF) SEBAGAI SUMBER PROTEIN HEWANI DALAM PAKAN IKAN - Andriani, Yuli; Pratama, Rusky Intan (Journal of Fish Nutrition, 2024)
Abundant organic waste has the potential to pollute the environment, so proper management is needed so that organic waste can become an economically valuable material. Bioconversion by maggot Hermetia illucens (Black Soldier Fly) is one of the effective methods to process organic waste into animal protein sources that can be used as fish and livestock feed. BSF maggot is able to reduce organic waste up to 78.9% per day and has a protein content of 30-45% and fat 24-30%. The maggot life cycle involves several phases from egg to adult, with temperature playing an important role in this process. Maggot also shows great potential in improving fish growth and health, and can be used as an efficient and highly nutritious alternative feed ingredient.